Data structures the fun way : from binary search to quadtrees in 100 cups of coffee - Kubica, Jeremy (No Starch Press, Inc., 2022)
"This accessible and entertaining book provides an in-depth introduction to computational thinking through the lens of data structures, a critical component in any programming endeavor. It will give you a strong background in implementing and working with more than 15 key data structures, from arrays, stacks, and queues to caches, bloom filters, skip lists, and graphs"--